Destination NATO defence reform in Bosnia and Herzegovina, 2003-13 - Maxwell, Rohan; Olsen, John Andreas (Whitehall paper series, 2013)
Defense reform has been a major component of Bosnia's stabilization and nation-building. Though true for many cases of post-conflict transition, it is especially so for Bosnia, which arguably has the most complex state structure in Europe. Ten years on from the start of Bosnia's defense-reform process, Destination NATO records and reviews the Bosnian experience of defense reform. The monograph offers policy-makers, practitioners and academics knowledge of the specific case of Bosnia and Herzegovina, and makes these insights relevant to defense-reform efforts in other contexts